2017
DOI: 10.1080/08916934.2017.1344972
|View full text |Cite
|
Sign up to set email alerts
|

Impaired salivary gland activity in patients with autoimmune polyendocrine syndrome type I

Abstract: Autoimmune polyendocrine syndrome type I (APS-I) is a severe disease caused by mutations in the autoimmune regulator (AIRE) gene. We hypothesized that salivary gland dysfunction could be a possible unexplored component of these patients and here aimed to investigate salivary and lachrymal symptoms in the Norwegian cohort of APS-I patients (N = 41) and the aetiology behind it. Sicca symptoms and possible corresponding underlying factors were assessed by subjective reports combined with objective measures of sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…As one of the key functions of IL-22 is to induce AMP secretion from epithelial cells in concert with IL-17A, it is possible that the secretion of these natural antibiotics is impaired in APECED patients. However, previous work has not found decreased beta and alpha defensin concentrations in APECED saliva samples (52). Our study confirmed abundant, and not impaired, LCN2 levels in the saliva of APECED patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As one of the key functions of IL-22 is to induce AMP secretion from epithelial cells in concert with IL-17A, it is possible that the secretion of these natural antibiotics is impaired in APECED patients. However, previous work has not found decreased beta and alpha defensin concentrations in APECED saliva samples (52). Our study confirmed abundant, and not impaired, LCN2 levels in the saliva of APECED patients.…”
Section: Discussionsupporting
confidence: 87%
“…However, we think that neither factor had impact on our analysis as none of the study subjects received immunosuppressive drugs, and only one patient was on antifungals, all other medications were only hormone replacements. Moreover, objective sicca symptoms are rare in European APECED patients and were reportedly present only in patients over 33 years of age (52). Our study included relatively young patients (17.7 ± 10.9 years) and none of them reported dry mouth.…”
Section: Discussionmentioning
confidence: 81%
“…Another disease with sicca symptoms is autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), a monogenic disorder caused by mutations in the AIRE transcription regulator leading to defective elimination of autoreactive T cells (Husebye et al 2018; Constantine and Lionakis 2019). Approximately 40% of APECED subjects exhibit SS-like sicca symptoms (designated here as APECED with sicca) by 30 y of age (Ferre et al 2016; Oftedal et al 2017). Consistent with autoimmune attack, immunofluorescence analysis revealed that 75% of APECED patients showed serum autoantibody immunoreactivity against the salivary gland (Oftedal et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most APS-1 patients develop disease components affecting the oral cavity; enamel hypoplasia and CMC are both common manifestations [9,15]. Also a Sjögren’s-like syndrome without extractable nuclear antigen autoantibodies has recently been described [15,16]. These oral manifestations probably interfere with the homeostasis of the oral microbiota.…”
mentioning
confidence: 99%